2016
DOI: 10.7567/jjap.55.02bc17
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in reliability of amorphous indium–gallium–zinc oxide thin-film transistors with Teflon/SiO2 bilayer passivation under gate bias stress

Abstract: The reliability of amorphous indium–gallium–zinc oxide (a-IGZO) thin-film transistors (TFTs) with Teflon/SiO2 bilayer passivation prepared under positive and negative gate bias stresses (PGBS and NGBS, respectively) was investigated. Heavier electrical degradation was observed under PGBS than under NGBS, indicating that the environmental effects under PGBS are more evident than those under NGBS. The device with bilayer passivation under PGBS shows two-step degradation. The positive threshold voltage shifts dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The V th shifts of a-IGZO TFTs without PVLs and with NC-PVLs were −1.98 and −1.90 V, respectively. As reported in previous research, it was confirmed that the V th of a-IGZO TFTs is scarcely affected by negative bias stress because a-IGZO TFTs is n-type. Therefore, in this research, influence for negative bias voltage was negligible.…”
Section: Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The V th shifts of a-IGZO TFTs without PVLs and with NC-PVLs were −1.98 and −1.90 V, respectively. As reported in previous research, it was confirmed that the V th of a-IGZO TFTs is scarcely affected by negative bias stress because a-IGZO TFTs is n-type. Therefore, in this research, influence for negative bias voltage was negligible.…”
Section: Results and Discussionsupporting
confidence: 85%
“…Consequently, these results show NC-PVLs have excellent barrier properties to prevent adsorption of oxygen and demonstrate an improved stability of a-IGZO TFTs. PBTS and NBTS tests at 50 °C were also conducted to verify the influence of temperature for organic PVLs and moisture in ambient air, respectively. , As shown in Figure , in the results of the PBTS test for a-IGZO TFTs without PVLs, with PMMA-PVLs, and with NC-PVLs, the values of positive V th shifts were 5.74, 4.77, and 3.88 V, respectively. In the results of the PBTS test, the stability of a-IGZO TFTs with NC-PVLs was improved up to 32 and 19% compared to PVLs ability of a-IGZO TFTs without PVLs and with PMMA-PVLs, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, for the stress duration of 5000 s, the V th of the TFT without passivation layer positively shifted by 1.02 V; in contrast, the V th of the TFT passivated by the AlO x passivation layer positively shifted by only 0.12 V. It was suggested that the adsorbed oxygen molecules could act as acceptor-ECS Journal of Solid State Science and Technology, 2021 10 045006 like states, which capture electrons leading to a positive V th shift. 39,40 As shown in Fig. 8b, the passivation can effectively prevent adsorbing O 2 molecules from the ambient, and thus the PBIS reliability is improved.…”
Section: Resultsmentioning
confidence: 98%
“…[8][9][10][11][12] Since a passivation layer is essential for improving the PBS reliability, many efforts have been made to understand the effects of the materials and deposition conditions of a passivation layer on the electrical properties and reliability of the IGZO TFTs. [13][14][15][16][17][18][19][20][21][22] To the best of our knowledge, there have been few research studies reported on the effect of the permeability of ambient molecules through the passivation layer on PBS reliability.…”
mentioning
confidence: 99%